The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1039/b9pp00177h
|View full text |Cite
|
Sign up to set email alerts
|

Mice drinking goji berry juice (Lycium barbarum) are protected from UV radiation-induced skin damage viaantioxidant pathways

Abstract: The goji berry, Lycium barbarum, has long been recognised in traditional Chinese medicine for various therapeutic properties based on its antioxidant and immune-modulating effects. This study describes the potential for orally consumed goji berry juice to alter the photodamage induced in the skin of mice by acute solar simulated UV (SSUV) irradiation. In Skh:hr-1 hairless mice, 5% goji berry juice significantly reduced the inflammatory oedema of the sunburn reaction. Dilutions of goji berry juice between 1% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
2
23
0
2
Order By: Relevance
“…Similar to the current results, they showed that dietary supplementation with anti-oxidants (daily vitamin C (L-ascorbic acid, 1000 mg) and vitamin E (RRR-alpha-tocopherol, 400 IU) supplementation) blunted the cortisol response to a single prolonged exercise challenge (Davison et al, 2007). Also, LBP has been shown to prevent oxidative stress following exhaustive exercise in rats (Shan et al, 2011) and the anti-inflammatory effect of Lycium barbarum consumption was demonstrated by Reeve et al (2010) in an animal model of UV radiation induced oxidative skin damage.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to the current results, they showed that dietary supplementation with anti-oxidants (daily vitamin C (L-ascorbic acid, 1000 mg) and vitamin E (RRR-alpha-tocopherol, 400 IU) supplementation) blunted the cortisol response to a single prolonged exercise challenge (Davison et al, 2007). Also, LBP has been shown to prevent oxidative stress following exhaustive exercise in rats (Shan et al, 2011) and the anti-inflammatory effect of Lycium barbarum consumption was demonstrated by Reeve et al (2010) in an animal model of UV radiation induced oxidative skin damage.…”
Section: Discussionsupporting
confidence: 76%
“…Several clinical studies, various pre-clinical in vivo animal and in vitro cell culture studies have shown the efficacy of L. barbarum and LBP as anti-oxidants in protecting against various peroxidationrelated conditions (Gong, Shen, Jin, Xing, & Tang, 2005;Huang, Lu, Shen, & Lu, 1999;Huang, Tian, Wang, Dong, & Wu, 2001;Huang, Yang, Wu, & Yan, 2003;Huang et al, 1998;Li, Ma, & Liu, 2007;Li, Yang, Ren, & Wang, 2002;Luo et al, 2006;Ni, Qing, Kaisa, & Lu, 2004;Reeve, Allanson, Arun, Domanski, & Painter, 2010;Ren, Ma, Shen, & Gao, 1995;Sui et al, 1996;Wang et al, 2002;Wu, Ng, & Lin, 2004;Zhang, 1993;Zhang, Zhang, & Li, 1997;Zhao, Alexeev, Chang, Greenburg, & Bojanowski, 2005).…”
Section: Anti-oxidant Effectsmentioning
confidence: 97%
“…One of them reports that ingesting the aqueous extract (juice) of LB protects mice from UV-induced damage, such as inflammatory oedema, immunosuppression, and sunburn reactions (Reeve et al 2010). Here also the antioxidant mechanism of action appears to be implicated, as quantified by the inhibition of lipid peroxidation.…”
Section: Skin Carementioning
confidence: 98%